2007
DOI: 10.1111/j.1439-0396.2006.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fusarium toxins on growth, humoral immune response and internal organs in weaner pigs, and the efficacy of apple pomace as an antidote

Abstract: A feeding trial using 220 weaner pigs which comprised two experimental series was conducted to investigate the effects of diets contaminated with the Fusarium toxins deoxynivalenol (DON) and zearalenone (ZON) and to test the hypothesis that apple pomace acts as an antidote to these mycotoxins. Two diets without contaminated wheat, containing either no pomace or 8% pomace, and two diets with naturally contaminated wheat (3.2 mg DON and 0.06 mg ZON, and 2.1 mg DON and 0.25 mg ZON per kg diet in series 1 and 2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…These results indicate a better G:F ratio in piglets fed the control or DON'PC diets compared with those on the other experimental diets. A decrease in G:F ratio has been previously observed for piglets fed a DON-contaminated diet (Rotter et al 1994;Swamy et al 2003;Gutzwiller et al 2007). The greater retention of Ca, or the absence of an effect for N and P deposition, when piglets were fed the DON-contaminated diet was associated with a reduction in the urinary excretion of N, P and Ca, except for piglets fed the DON' PC diet.…”
Section: Effects Of Don and Anti-mycotoxin Additives On Digestibilitymentioning
confidence: 63%
“…These results indicate a better G:F ratio in piglets fed the control or DON'PC diets compared with those on the other experimental diets. A decrease in G:F ratio has been previously observed for piglets fed a DON-contaminated diet (Rotter et al 1994;Swamy et al 2003;Gutzwiller et al 2007). The greater retention of Ca, or the absence of an effect for N and P deposition, when piglets were fed the DON-contaminated diet was associated with a reduction in the urinary excretion of N, P and Ca, except for piglets fed the DON' PC diet.…”
Section: Effects Of Don and Anti-mycotoxin Additives On Digestibilitymentioning
confidence: 63%
“…In addition, this work shows that micronized fibres obtained from almond and artichoke by‐products can also act as broad‐spectrum mycotoxin adsorbents. Previous studies reported that micronized wheat fibres exhibited beneficial effects against OTA adsorption in rats, while apple pomace (rich in fibres and pectin) incorporated in DON‐contaminated feed attenuated the negative effects of this mycotoxins in pigs . Furthermore, water extract of artichoke showed significant protective effects against the growth inhibitory effect of OTA and associated pathomorphological changes in chicks .…”
Section: Resultsmentioning
confidence: 93%
“…Previous studies reported that micronized wheat fibres exhibited beneficial effects against OTA adsorption in rats, 18,19 while apple pomace (rich in fibres and pectin) incorporated in DON-contaminated feed attenuated the negative effects of this mycotoxins in pigs. 36 Furthermore, water extract of artichoke showed significant protective effects against the growth inhibitory effect of OTA and associated pathomorphological changes in chicks. 37 Interesting findings were also obtained from in vitro studies regarding humic acids, originating from natural decaying of organic plant materials.…”
Section: Screening Of Food Plants and By-products As Multi-toxin Adsomentioning
confidence: 95%
“…Animal studies have shown that DON may induce generalized GI tract toxicity, emetic effects and feed refusal [4][5][6]. Studies in animal models and immortalized cell lines have also shown that DON exposure modulates immune function by specifically influencing proinflammatory responses and white blood cell distribution and proliferation in several organs [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%